2021
DOI: 10.3390/buildings11040175
|View full text |Cite
|
Sign up to set email alerts
|

Development of Side Mold Control Equipment for Producing Free-Form Concrete Panels

Abstract: Free-form concrete panel production requires an increasing amount of manpower because the molds cannot be reused. There are many limitations when it comes to reproducing accurate forms due to the many manual processes. Therefore, the current study developed side mold control equipment that can automatically fabricate molds for free-form concrete panels. The equipment is capable of molding various shapes and sustainable operation. However, there may be errors as it automatically produces various shapes. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The use of EPS as moulds to cast concrete has been in the construction industry for a long time whereby, they are used as prefabricated and in-situ concrete (Martins et al, 2015). Additionally, the usage of EPS mould in this study was its cost-effectiveness in moulding complex concrete forms (Seo & Hong, 2017;Yun et al, 2021). In this experiment, both greased and ungreased EPS designs produced similar results after demoulding.…”
Section: Expanded Polystyrene (Eps Foam) Mouldmentioning
confidence: 77%
See 1 more Smart Citation
“…The use of EPS as moulds to cast concrete has been in the construction industry for a long time whereby, they are used as prefabricated and in-situ concrete (Martins et al, 2015). Additionally, the usage of EPS mould in this study was its cost-effectiveness in moulding complex concrete forms (Seo & Hong, 2017;Yun et al, 2021). In this experiment, both greased and ungreased EPS designs produced similar results after demoulding.…”
Section: Expanded Polystyrene (Eps Foam) Mouldmentioning
confidence: 77%
“…EPS moulds were selected because they are frequently employed to create geometrically shaped or complex designs. However, they are often utilized for a single test as they must be torn apart when demoulding the specimen (Mohammadi et al, 2014;Yun et al, 2021). While comparatively weak, they offer insulation and protection from vibration for freshly foamed concrete cubes (Coombes & Naylor, 2011;Coombes et al, 2017).…”
Section: Expanded Polystyrene (Eps Foam) Mouldmentioning
confidence: 99%
“…As to the scope of this study, the suggested radiant heater is applicable to the multi-point CNC equipment developed in the papers of Jeong and Yun [6,7]. This study intends to improve the productivity and economical efficiency of FCP by shortening the curing time in FCP production.…”
Section: Scope and Methods Of Researchmentioning
confidence: 99%
“…Most of the studies on the FWS selection problem from 1989 until 2012 considered the FWS selection criteria under the four main groups identified by Hanna [15]. The widespread use of industrial FWSs in building construction projects across the world, as well as new technological advancements in formwork engineering [22,23], necessitated the inclusion of additional criteria in the FWS selection process in the following years. For instance, Krawczyska-Piechna [24] and Krawczyska-Piechna [25] contributed to the relevant literature by introducing criteria, such as flexibility, durability, compatibility, safety, and weight of the FWS for building construction projects in Poland.…”
Section: Studies Related To the Identification And/or Ranking Of Fws ...mentioning
confidence: 99%